Anti-DFS70 as Nonsystemic Autoimmune (Primary Billiar Cholangitis) Concomitant Disease Marker in Systemic Lupus Erythematosus - Putra, Yasjudan Rastrama; Mulya, Deshinta Putri; Indrarti, Fahmi (Jurnal Penyakit Dalam Indonesia, 2020)
Anti-dense fine speckled 70 (DFS70) is known as a non-systemic autoimmune marker. It is only found in 1% of systemic autoimmune patients and 2–22% in healthy population. To the best of our knowledge, no anti-DFS70 positive has been reported in systemic lupus erythematosus (SLE) patients with primary billiary cholangitis (PBC) comorbidities. We reported a 40-year-old woman that was diagnosed with SLE 1-month before, came to the hospital due to seven days of fatigue, loss of appetite, icteric, arthralgia, hair loss, and unexplained fever. Total bilirubin was 9.46 mg/dl, direct bilirubin 7.73 mg/dl, gamma-glutamyl transferase (GGT) 503 U/L, alkaline phosphatase (ALP) 520 U/L, ANA-IF 1:1000, ANA-profile measurement borderline on the anti-centromere B, and three positives on the DFS70. Magnetic resonance cholangiopancreatography (MRCP) shown the PBC feature. After ursodeoxycholic acid (UDCA) therapy 250 mg twice daily, ALP and GGT backed to normal limits within two months. This case reminds the doctor that anti-DFS70 finding in SLE needs further evaluation, whether other nonsystemic autoimmune exist or not. Concomitant PBC with SLE well responded with UDCA standard therapy.